A comparative study of academic teaching of Islam in Nigerian universities (2010)
This paper attempts to examine the inner dialectics in the teaching of Islam in some selected Nigerian Universities with a special focus on Crescent University of Abeokuta, Nigeria. A comparison is made between the teaching of Islam there and at other universities involved in the academic study of Islam, especially in south-western Nigeria. One common factor to the teaching of Islam in these universities is the illusion of logic, philosophy and critical thinking in the curriculum, which is a major strong point that has contributed to its relevance and grow in Nigerian academia. But while Al-Hikmah and other Nigerian universities are fully teaching the twin disciplines of Arabic and Islamic Studies especially in the case of Al-Hikmah since the universities rose from a former College of Arabic and Islamic Studies. Crescent University takes after the International Islamic University Malaysia, on the other hand, is engaged currently in teaching Islam both as a general university course and with other subject combinations.